THE ROLE OF THE STATE IN FINANCING THE HIGHER EDUCATION SYSTEM - Karaev Payzillakhon Yusufxonovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article analyzes modern theories of financing higher education institutions and their specific aspects. Scientific conclusions on the role of state and state budget funds in financing the higher education system have been formed. Based on the research, scientific suggestions and recommendations aimed at improving the role of the state in financing the higher education system were developed.